Sensory abnormalities in children with autism spectrum disorder - Annio Posar; Paola Visconti (Elsevier, 2018)
Objective: The clinical picture of children with autism spectrum disorder is characterized by deficits of social interaction and communication, as well as by repetitive interests and activities. Sensory abnormalities are a very frequent feature that often go unnoticed due to the communication difficulties of these patients. This narrative review summarizes the main features of sensory abnormalities and the respective implications for the interpretation of several signs and symptoms of autism spectrum disorder, and therefore for its management. Sources: A search was performed in PubMed (United States National Library of Medicine) about the sensory abnormalities in subjects (particularly children) with autism spectrum disorder. Summary of the findings: Sensory symptoms are common and often disabling in children with autism spectrum disorder, but are not specific for autism, being a feature frequently described also in subjects with intellectual disability. Three main sensory patterns have been described in autism spectrum disorder: hypo-responsiveness, hyper-responsiveness, and sensory seeking; to these, some authors have added a fourth pattern: enhanced perception. Sensory abnormalities may negatively impact the life of these individuals and their families. An impairment not only of unisensory modalities but also of multisensory integration is hypothesized. Conclusions: Atypical sensory reactivity of subjects with autism spectrum disorder may be the key to understand many of their abnormal behaviors, and thus it is a relevant aspect to be taken into account in their daily management in all the contexts in which they live. A formal evaluation of sensory function should be always performed in these children. Resumo: Objetivo: O quadro clínico de crianças com transtorno do espectro do autismo é caracterizado por déficits de interação social e comunicação, bem como por interesses e atividades repetitivos. As alterações sensoriais são uma característica muito frequente que geralmente não é percebida devido às dificuldades de comunicação desses pacientes. Nesta análise narrativa, resumimos as principais características de alterações sensoriais e as respectivas implicações para a interpretação de vários sinais e sintomas do transtorno do espectro do autismo e, portanto, para seu manejo. Fontes: Realizamos uma busca no PubMed (Biblioteca Nacional de Medicina dos Estados Unidos) sobre as alterações sensoriais em indivíduos (principalmente crianças) com transtorno do espectro do autismo. Resumo dos achados: As alterações sensoriais são comuns e geralmente invalidam as crianças com transtorno do espectro do autismo, porém não são específicas do autismo, sendo uma característica frequentemente descrita também em indivíduos com deficiência intelectual. Três principais padrões sensoriais foram descritos no transtorno do espectro do autismo: hiporreatividade, hiperreatividade e busca sensorial; a eles, alguns autores acrescentaram um quarto padrão: percepção aprimorada. As alterações sensoriais podem afetar negativamente a vida desses indivíduos e de suas famílias. Hipotetizamos uma deficiência não apenas das modalidades não sensoriais, mas também da integração multissensorial. Conclusões: A reatividade sensorial atípica de indivíduos com transtorno do espectro do autismo pode ser a chave para entender muitos de seus comportamentos anormais e, portanto, é um aspecto relevante para ser considerado em seu manejo diário em todos os contextos nos quais eles vivem. Sempre se deve fazer uma avaliação formal da função sensorial nessas crianças. Keywords: Autism spectrum disorder, Sensory reactivity, Sensory abnormalities, Sensory seeking, Palavras-chave: Transtorno do espectro autista, Reatividade sensorial, Alterações sensoriais, Busca sensorial